"I LEAVE YOU LOVE": African American Women as Collectors in, of, and through, the Arts. Issue 2 (June 2019) - Brevard, Lisa Pertillar
In her last will and testament, educator-activist Mary McLeod Bethune (1875–1955) declared, "I LEAVE YOU LOVE. Love builds." A direct descendant of former chattel slaves, Bethune believed in building from the bottom up: beginning with love, or positive thoughts, and manifesting those thoughts. By accretion of goods and goodwill, she built not only a physical school which fostered the arts as a bridge toward world citizenship for disenfranchised black people but also a school of thought, extending to encompass purposeful government service at local and federal levels, toward achieving a just society. Bethune's determined example of building by accretion informs and helps us to better understand and articulate a wide variety of African American women's collecting in, of, and through, the arts. This article explores and defines—according to philosophy, purpose, practice, type, scope, and audience—various examples of collecting and collections among selected African American women in the arts, many of whom became contributors to, and subjects of, various collections.